PENGEMBANGAN POTENSI WISATA BERBASIS COMMUNITY BASED TOURISM (CBT) UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT DI DESA BETTENG KECAMATAN PAMBOANG - Haeruddin Hafid; Sufyan Amirullah; Sri Amalia Edy (Universitas Mataram, 2023)
Betteng Village is one of the villages that has tourism potential because of its geographical location in a mountainous area. The tourism potential it has is called